Higher frailty levels are associated with lower cognitive test scores in a multi-country study: evidence from the study on global ageing and adult health - García-Chanes, Rosa Estela; Avila-Funes, José Alberto; Borda, Miguel Germán; Pérez-Zepeda, Mario Ulises; Gutiérrez-Robledo, Luis Miguel (Frontiers in Medicine, 2023)
Background Frailty has been recognized as a growing issue in older adults, with recent evidence showing that this condition heralds several health-related problems, including cognitive decline. The objective of this work is to determine if frailty is associated with cognitive decline among older adults from different countries. Methods We analyzed the baseline the Study on Global Ageing and Adult Health (SAGE), that includes six countries (Ghana, South Africa, Mexico, China, Russia, and India). A cross-section analysis was used to assess how Frailty was related with the Clinical Frailty Scale decision tree, while cognitive decline was evaluated using standardized scores of tests used in SAGE. Results A total of 30,674 participants aged 50 years or older were included. There was an association between frailty levels and cognitive performance. For example, women had an inverse relationship between frailty levels and cognitive scores, even when comparing robust category with frailty level 2 (RRR = 0.85; p = 0.41), although the relative risks decrease significantly at level 3 (RRR = 0.66; p = 0.03). When controlling for age, the relative risks between frailty levels 4 to 7 significantly decreased as cognitive performance increased (RRR = 0.46, RRR = 0.52, RRR = 0.44, RRR = 0.32; p < 0.001). Conclusion Our results show an association between frailty levels measured in a novel way, and cognitive decline across different cultural settings.